Efficacy and safety of cadonilimab combined with AG chemotherapy in patients with unresectable locally advanced or metastatic pancreatic ductal adenocarcinoma: a retrospective real-world study - Qin, Wenke; Du, Yan; Zhao, Xuean; Zhao, Yongqing; Zhang, Yan; Zhang, Shuze; Yang, Zengxi; Li, Xin; Niu, Jubao; Zhao, Dewen; Wei, Kongyuan; Zhang, Hui (Frontiers in Immunology, 2025)
BackgroundAt the time of diagnosis, 80% of patients with pancreatic ductal adenocarcinoma (PDAC) are already at an unresectable advanced stage. The median overall survival (mOS) with traditional AG chemotherapy is only 8.5 months. The bispecific antibody Cadonilimab targeting PD-1 and CTLA-4 has shown immuno-oncological synergy in solid tumors, but evidence in PDAC is limited.MethodsThis study is a single-center retrospective study that included 14 patients with advanced pancreatic ductal adenocarcinoma. These patients received Cadonilimab (10 mg/kg, Q3W) in combination with AG chemotherapy. The primary endpoint was the disease control rate (DCR, RECIST 1.1).ResultsThe disease control rate (DCR) reached 85.7%, and the objective response rate (ORR) was 14.3%; the median progression-free survival (mPFS) was 7.87 months, and the median overall survival (mOS) was 11.45 months. Among patients with a decrease in CA19-9, the median overall survival was significantly prolonged (12.92 vs 8.89 months, P = 0.027); patients with a platelet-lymphocyte ratio (PLR) ≤ 165.62 had a significantly better mOS (12.37 vs 8.74 months, P = 0.025). Although the incidence of grade 3 treatment-related adverse events was 57.1%, no grade 4 treatment-related toxic events were observed.ConclusionIn conclusion, cadonilimab combined with AG chemotherapy demonstrated promising antitumor activity and manageable safety in PDAC. Dynamic monitoring of PLR and CA19–9 may aid efficacy evaluation, but these exploratory findings require confirmation in prospective multicenter trials.